Microplastics in beluga whales (Delphinapterus leucas) from the Eastern Beaufort Sea. (January 2020) - Moore, R.C.; Loseto, L.; Noel, M.; Etemadifar, A.; Brewster, J.D.; MacPhee, S.; Bendell, L.; Ross, P.S.
Abstract: Microplastics (MPs, particles <5 mm) represent an emerging global environmental concern, having been detected in multiple aquatic species. However, very little is known about the presence of MPs in higher trophic level species, including cetaceans. We worked with community based monitors and Inuvialuit hunters from Tuktoyaktuk (Northwest Territories, Canada) to sample seven beluga whales ( Delphinapterus leucas ) in 2017 and 2018. Microplastics were detected in the gastrointestinal tracts in every whale. We estimate that each whale contained 18 to 147 MPs in their GI tract (average of 97 ± 42 per individual). FTIR-spectroscopy revealed over eight plastic polymer types, with nearly half being polyester. Fibres made up 49% of MPs. The diversity of MP shapes and polymeric identities in beluga points to a complex source scenario, and ultimately raises questions regarding the significance and long-term exposure of this pollutant in this ecologically and culturally valuable species. Highlights: Microplastic particles (MPs) were found in all seven belugas harvested by Inuvialuit hunters. Both fibres and fragments were found within stomachs and intestines, with all particles being <5 mm in size. Nearly half of particles found were identified as PET (Polyethylene terephthalate). Exposure pathways and health implications remain unclear.